BENTUK-BENTUK KOMUNIKASI DALAM PEMBELAJARAN - Rahman, Ali (Paedagogia: Jurnal Pendidikan, 2016)
Communication is the act of providing information to others with the intention that other people have similar information with its message. Communication can be done with one-way or two-way/multi direction. The message conveyed by the sender to the recipient may be packaged verbal or nonverbal. Verbal communication is communication that uses words, spoken or written. Nonverbal communication is communication that is packaged in a message without words. Communication views of the participants were divided into communication intrapersonal communication, interpersonal communication, group communication, mass communication, and organizational communication. Learning is an activity that involves a person in an attempt to acquire the knowledge, skills and positive values ​​by utilizing a variety of resources for learning. Learning can involve two parties, namely students and teachers as facilitators. Learning occurs in learning and teaching process. Thus, learning requires interaction shows that the learning process is a process of communication, meaning that inside there is a process of delivering a message by the teacher to the student.